SME e-cooperation: a theoretical team contract analysis under hidden information - Alderete, Maria Veronica (2012)
Virtual Cooperation among SME firms can be analyzed from different theoretical perspectives. This paper considers e-cooperation among firms under asymmetric information. Firms cooperate jointly to produce some output or service, and they organize in teams whose firms’ characteristics are imperfectly observed. Suppose firms can observe their efforts or actions but they cannot observe the disutility of effort which they can discover after the contract is signed. The objective of this paper is to analyze virtual cooperation contracts under hidden information based on the original papers of Holmstrom (1982) and Rasmussen (1987). Some conditions are derived under which it is possible to implement an optimal sharing rule for a virtual team of SME under a hidden information frame.